Incidence and disease burden of chemotherapy-induced peripheral neuropathy in a population-based cohort - Shah, Arya; Hoffman, E Matthew; Mauermann, Michelle L; Loprinzi, Charles L; Windebank, Anthony J; Klein, Christopher J; Staff, Nathan P (Journal of neurology, neurosurgery and psychiatry, 2018)
ObjectiveTo assess disease burden of chemotherapy-induced peripheral neuropathy (CIPN), which is a common dose-limiting side effect of neurotoxic chemotherapy. Late effects of CIPN may increase with improved cancer survival.MethodsOlmsted County, Minnesota residents receiving neurotoxic chemotherapy were identified and CIPN was ascertained via text searches of polyneuropathy symptoms in the medical record. Clinical records were queried to collect data on baseline characteristics, risk factors, signs and symptoms of CIPN, medications, impairments and International Classification of Diseases, Ninth Revision (ICD-9) diagnostic codes for all subjects.ResultsA total of 509 individuals with incident exposure to an inclusive list of neurotoxic chemotherapy agents between 2006 and 2008 were identified. 268 (52.7%) of these individuals were determined to have CIPN. The median time from incident exposure to first documented symptoms was 71 days. Patients with CIPN received a neuropathy ICD-9 diagnosis in only 37 instances (13.8%). Pain symptoms and use of pain medications were observed more often in patients with CIPN. Five-year survival was greater in those with CIPN (55.2%) versus those without (36.1%). Those with CIPN surviving greater than 5 years (n=145) continued to have substantial impairments and were more likely to be prescribed opioids than those without CIPN (OR 2.0, 1.06–3.69).ConclusionsResults from our population-based study are consistent with previous reports of high incidence of CIPN in the first 2 years following incident exposure to neurotoxic chemotherapeutic agents, and its association with significant pain symptomatology and accompanied long-term opioid use. Increased survival following exposure to neurotoxic chemotherapy and its long-term disease burden necessitates further study among survivors.